Decellularization of porcine urethral tissue using chemical immersion with sonication - Galindez, Sofia Aidrianne Marina (Animo Repository, 2022)
The urethra plays a key role in the excretory system as its outlet and is prone to complications such as infections, damage, strictures, and trauma. A potential solution to these problems is the development of acellular urethral scaffolds via decellularization. Perfusion decellularization produces acellular tissue scaffolds that requires long treatment time and excessive chemical consumption if performed alone. To address this, the combination of chemical immersion and sonication is used to decellularize porcine urethras. The addition of sonication will reduce the decellularization time but has the potential to damage the surface morphology of the porcine urethra. With this, the effects of sonication at varying power levels on the decellularization time, cell removal, and surface morphology were determined. A 2.0-cm section of a porcine urethra was immersed in a 0.5% SDS solution and treated with different sonication power levels (0 W, 60 W, 120 W, and 180 W). The decellularization time was measured by the change in color from pinkish red to translucent white. The extent of cell removal of the scaffold by hematoxylin and eosin (H&E) staining and DNA quantification, and its surface morphology by scanning electron microscopy (SEM), were analyzed. It was found that as the sonication power increases, the average decellularization time decreases, with the longest time being 29.5 hours for immersion alone and the shortest time being 2.5 hours for immersion with sonication at 180 W. The results from histological analysis and DNA quantification proved the percentage of cellular removal (99.50 ± 0.1585%) and that there is no statistical significance between the DNA concentration and power levels. The SEM imaging of the native and acellular urethral tissues detailed the structural preservation at low sonication power and moderate disorganization at high sonication power levels. The use of immersion decellularization with sonication produced acellular urethral scaffolds, which can be used for urethral treatment and reconstruction.